Prematch salivary secretory Immunoglobulin A in soccer players from the 2014 World Cup qualifying campaign - Morgans, R.; Owen, A.; DorD. A.; Drust, B.; Morton, J. P (International Journal of Sports Physiology and Performance, 2015)
Purpose: To monitor resting salivary secretory immunoglobulin A (SIgA) levels in international soccer players during the short-term training period that precedes international match play. Methods: In a repeated-measure design, saliva samples were obtained from 13 outfield soccer players who participated in the training camps preceding 7 games (5 home and 2 away) of the 2014 FIFA World Cup qualifying campaign. Samples were obtained daily for 4 d preceding each game (and analyzed for SIgA using the IPRO oral-fluid-collection system) at match day minus 1 (MD-1), minus 2 (MD-2), minus 3 (MD-3), and minus 4 (MD-4). Results: SIgA displayed a progressive decline (P = .01) during the 4-d training period (MD-4, 365 ± 127 µg/mL; MD-3, 348 ± 154 µg/mL; MD-2, 290 ± 138 µg/mL; MD-1, 256 ± 90 µg/mL) such that MD-1 values were significantly lower (P = .01) than both MD-4 and MD-3. The 95% confidence intervals for the differences between MD-1 and MD-4 were -191 to -26 and between MD-1 and MD-3 were -155 to -28. Conclusions: Data demonstrate that a short-term soccer-training camp in preparation for international competition induces detectable perturbations to mucosal immunity. Future studies should monitor SIgA (as a practical and noninvasive measure of immunity) alongside internal and external measures of training load in an attempt to strategically individualize training and nutritional strategies that may support optimal preparation for high-level competition.